Study of Ontology, Epistemology, and Axiology of the Cooperative Integrated Reading and Composition (CIRC) Learning Model for Indonesian Language Education - Pradita, Duta Risma; Rohman, Novia; Amalia, Dwi Sarifatul; Zamzami, Maulida Alif Nurul; Setiawaty, Rani (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: The purpose of this study is to analyze the ontological, epistemological, and axiological reflections of the “Cooperative Integrated Reading and Composition (CIRC)” learning model in the context of English language learning. Background Problems: The implementation of the CIRC model has so far only focused on practical aspects, without discussing in depth the nature of science, the learning process, and its educational values. Novelty (optional): This study presents something new, namely an in-depth study of the CIRC model from a philosophical perspective in the Indonesian. Research Methods: Data were obtained from 25 selected national journal articles (2015–2025) identified using the keyword “CIRC model” through the Publish or Perish (PoP) application, with selection stages including identification, assessment, and synthesis of findings. Finding/Results: 1) Ontology reveals that knowledge in the CIRC model is created collaboratively through direct interaction between students in small heterogeneous groups (4-5 students). 2) Epistemology, namely the learning process is carried out in three sequential stages starting from preparation, practice to evaluation. 3) The axiology of the CIRC learning model, namely it can improve students' reading and writing literacy, develop critical thinking skills, and strengthen collaborative skills with an open attitude between students. Conclusion: The CIRC model is an innovative, holistic model, relevant to strengthening Indonesian language learning, and has the potential to accommodate diverse student abilities.